Investigating Customer Satisfaction on “Whoosh” High-Speed Train Services Using Importance Performance Analysis and Customer Satisfaction Index - Achmadi, Rudhi; Widiarto, Setyo (Asian Journal of Management, Entrepreneurship and Social Science, 2025)
This study aims to determine the level of satisfaction of Whoosh high-speed train service customers with the services provided by KCIC management. The "Whoosh" is a high-speed rail owned by Indonesia connecting Jakarta and Bandung. It is Southeast Asia's first high-speed railway. The study used primary data collected using a questionnaire on a Likert scale of 1 to 5, with 240 respondents using the Whoosh high-speed train service. The obtained data was processed with Microsoft Excel and SPSS software. The data was then analyzed using the Importance-Performance Analysis (IPA) and the Customer Satisfaction Index. Furthermore, the findings of the CSI study revealed that in general, the degree of satisfaction of service customers was at an index value of 81.07%. Keywords: Customer Satisfaction, Customer Satisfaction Index (CSI), Importance-Performance Analysis (IPA), Whoosh.